2020
DOI: 10.1002/num.22476
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and numerical approaches to nerve impulse model of fractional‐order

Abstract: We consider a fractional-order nerve impulse model which is known as FitzHugh-Nagumo (F-N) model in this paper. Knowing the solutions of this model allows the management of the nerve impulses process. Especially, considering this model as fractional-order ensures to be able to analyze in detail because of the memory effect. In this context, first, we use an analytical solution and with the aim of this solution, we obtain numerical solutions by using two numerical schemes. Then, we demonstrate the walking wave-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(32 citation statements)
references
References 42 publications
0
31
0
1
Order By: Relevance
“…First, it may be observed that Figures 1 and 2 are singular complex wave solutions to the governing model, Figures 3 and 4 are periodic complex wave solutions for the Equation (1).Unlike many analytical methods, we offer different solutions from the (1/G )-expansion method [25][26][27][28] which produces hyperbolic type traveling wave solution. What is interesting here is the idea that at the beginning, if m = 0, the solutions produced by the (1/G )-expansion method are obtained.…”
Section: Resultsmentioning
confidence: 99%
“…First, it may be observed that Figures 1 and 2 are singular complex wave solutions to the governing model, Figures 3 and 4 are periodic complex wave solutions for the Equation (1).Unlike many analytical methods, we offer different solutions from the (1/G )-expansion method [25][26][27][28] which produces hyperbolic type traveling wave solution. What is interesting here is the idea that at the beginning, if m = 0, the solutions produced by the (1/G )-expansion method are obtained.…”
Section: Resultsmentioning
confidence: 99%
“…We conclude from the results of Equations (18) and (19) that the iterative process used is stable. The predictor corrector Adams Bashforth-Moulton method is now available for a system solution based on an equal (10) in References [40][41][42][43][44][45].…”
Section: Liouville-caputo Sensementioning
confidence: 99%
“…Lineer olmayan kısmi türevli diferansiyel denklemlerden; plazma fiziği [1,2], akışkanlar mekaniği [3], fiber optik [4] ve birçok bilim alanında yararlanılmaktadır. Bu denklemlerin çözümlerini elde etmek için nümerik ve analitik metotlar geliştirilmiştir [5]. Bu metotlardan; Varyasyonel İterasyon Metot [6,7], Homotopi Analiz Metot [8], Homotopi Pertürbasyon Metot [9][10][11], Adomian Ayrışım Metot [12], Homojen Denge Metot [13][14][15][16][17][18][19][20][21][22][23][24] ve diğerleri son yirmi yılda litaratürde bulunan çalışmalardandır.…”
Section: Introductionunclassified